Perencanaan Ulang Struktur Atas Bangunan Kantor Dinas Pangan Provinsi Sumatera Barat - Frengki Jasmanto (Jurnal Teknologi, 2020)
Upper structure is a building structure that is above the ground level such as columns, beams and floor plates. Each of thesecomponents has a different function in a structure. The reason for the appointment of this title is because the dimensions and useof reinforcement in this structure are inefficient and too wasteful. Therefore this title was appointed as a case study with the aim of planning the dimensions and structural reinforcement consisting of column elements, beams and floor plates in an efficient Padang city food office building and reviewing the structural design due to the use of reinforcement and dimensions too over or wasteful. . The method used in dimensioning and calculating reinforcement uses the SAP 2000 v14 method. With a design load that includes dead load, live load, and earthquake load in accordance with SNI 1727-2013 regarding the minimum load for planning buildings and other structures. Overall, the construction structure of this building is quite complex to discuss due to the additional roof load in the form of a helipad. From the results of this discussion, dimensions and structural reinforcement are more efficient and reduce construction costs, without reducing the quality and function theyshould be..